DANA PIHAK KETIGA, KECUKUPAN MODAL DAN LIKUIDITAS TERHADAP PEMBIAYAAN MUDHARABAH DENGAN PEMBIAYAAN BERMASALAH SEBAGAI PEMODERASI - Elan Kurniawan; Komisah Nurhidayah (AKRUAL : Jurnal Akuntansi dan Keuangan, 2020)
This Purpose of this study aims to examine the effect of Third party funds, capital adequacy ratio and liquidity on mudharabah financing with non performing financing as Moderating in Islamic commercial bans in Indonesia for the 2014-2019. The Samples were taken using a purposive sampling method with certain criteria, during the study period. Based on the criteria set by panel data usage, 54 data can be processed. The analytical method used is multiple linear regression processed using Eviews 9. The results of this study indicate that: Third party funds have a positive effect on mudharabah financing, capital adequacy ratio have a positive effect on mudharabah financing, liquidity has no effect on mudharabah financing, Third party fund trough non performing financing have effect mudharabah financing.Capital adequacy ratio moderated through non performing financing has no effect on mudharabah, lLiquidity moderated through non performing financing has an effect on mudharabah financing.